Environmental policy, spatial spillovers and the emergence of economic agglomerations - Efthymia Kyriakopoulou; Anastasios Xepapadeas (Fondazione Eni Enrico Mattei (FEEM), 2009)
We explain the spatial concentration of economic activity, in a model of economic geography, when the cost of environmental policy - which is increasing in the concentration of emissions - and an immobile production factor act as centrifugal forces, while positive knowledge spillovers and iceberg transportation costs act as centripetal forces. We study the agglomeration effects caused by trade-offs between centripetal and centrifugal forces. The above effects govern firms' location decisions and as a result, they define the distribution of economic activity across space. We derive the rational expectations equilibrium and the social optimum, compare the outcomes and characterize the optimal spatial policies.
Keywords: R3; Q5; H2; 330; Agglomeration; Spatial Economics; Environmental Policy; Knowledge Spillovers; Transportation Cost